A Flexible Modular Housing System Considering User Preference - Focused on Single-Family Houses for the Elderly- - Yeop Park, Seung; Hee Chung, Jae; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study aims to propose a flexible modular housing system that takes into account the user preference according to lifestyles and lifecycle of the elderly.Methods/Statistical Analysis: This study, through the precedent research and theoretical consideration, analyzes the behaviors of the elderly, the characteristics of their housing, and the housing planning technique, especially regarding modular housing, and derives flexible housing planning elements. Analysis of the behavior of the elderly and the characteristics of their housing shows that they have specific preferences for the type of housing flexibility they desire, which can be fulfilled by modular housing. Findings: Based on the analysis of the characteristics of the elderly and flexible housing plan, a system is configured comprising elements of transformation, addition, and deletion that can be disassembled and recombined according to the behaviors and life types of the elderly. The prototypes are developed for three stages: an independent couple in their sixties, a dependent couple in their seventies, and a dependent single in their eighties, depending on the 10-year lifecycle. In each step, transformation, addition, and deletion are applied separately, and flexible modular housing prototypes are suggested according to the lifestyles and lifecycle of residents. Much research has been published on the topic of elderly housing, but there have been few integrated studies that propose flexible housing plans that adapt to the life types of the elderly. In addition, there is little research on single-family houses, where many elderly people live. This study is distinct from previous studies, as it presented a flexible modular housing system considering user preference according to lifestyles and lifecycle of the elderly.Improvements/Applications: This study provides a platform upon which the scope of research can be expanded, and prototypes customized for other users, such as young people, will be suggested in the future.Â Â